A decade of FDA approvals for pediatric cancer indications: What have we learned? - Marjorie E. Zettler (EJC Paediatric Oncology, 2023)
Objective: The present analysis reviews a decade of cancer drug approvals for pediatric indications in the United States, and aims to determine the impact of legislative initiatives, including the Pediatric Research Equity Act (PREA), the Research to Accelerate Cures and Equity (RACE) for Children Act, the Best Pharmaceuticals for Children Act (BPCA), and the Rare Pediatric Disease Priority Review Voucher Program. The implementation of 2 strategies designed to improve the efficiency of drug development, use of real-world data (RWD) and use of pediatric extrapolation, are also evaluated. Methods: Review packages, approval letters and prescribing information for cancer drugs receiving original or supplementary Food and Drug Administration (FDA) approval 2012–2021 were retrieved from Drugs@FDA. Details of the approvals, indication, and requirements for pediatric trials were extracted. Results: A total of 39 (11.4%) of the 341 original and supplementary oncology drug approvals were for pediatric indications. None resulted from trials mandated by PREA or the RACE Act; 4 resulted from trials conducted pursuant to a written request under BPCA; and 3 were granted Rare Pediatric Disease Priority Review Vouchers. More than a third included RWD with their submission, and more than half relied on extrapolation for the approved pediatric indication. Conclusions: Few cancer drug approvals for pediatric indications from 2012 to 2021 are attributable to legislative initiatives, but use of RWD and extrapolation was common. New legislation and continued advances in regulatory science have the potential to further translate advances in precision medicine into new treatments for children with cancer.